Dengue fever presenting as acute pancreatitis - Kumar, Surendra; Lakhiwal, Rajkumar; Bhandiwad, Chandrashekhar; Chhimpa, Atmaram; Gupta, Akhil (International Journal of Research in Medical Sciences, 2017)
A 32-year-old non-alcoholic female was admitted with complaints of severe abdominal pain and was diagnosed with acute pancreatitis after blood investigations and USG of the abdomen. She had fever on the initial two days of admission, and serology tested positive for dengue. Treatment for dengue was instituted, leading to a good response and complete resolution of pancreatitis. The patient has been doing well and has had no recurrence of pancreatitis.